The influence of family business background on the entrepreneurial intention of individuals. A quantitative study of Hungarian university students - Szabó, Krisztofer; Aranyossy, Márta (Society and economy, 2024)
With an overall aim of providing insights into fostering an entrepreneurial mindset and promoting economic development, researchers have devoted notable attention to intentional and motivational factors for starting businesses, as well as those influencing processes from idea generation to the realisation of a new business. This research project aims to investigate the influence of family business background on entrepreneurial intention. One of the novel features of the approach is the rigorous statistical exploration of direct and moderating effects of family business background while accounting for other factors influencing entrepreneurial intention. The analysis is based on a survey of 590 active university students studying business and economics in the seven largest universities in Hungary. Hierarchical regression analysis was applied to examine how the existence of family business background can influence and moderate relationships between individual factors and entrepreneurial intention. Results confirm that family business background has a significant positive impact on entrepreneurial intention and is most likely to exert its impact through increased human capital levels, entrepreneurial knowledge, skills and experience. The findings not only contribute to accumulated knowledge of the interdisciplinary family entrepreneurship field, but also have policy and educational implications.